Coverage of the consumption of nyaope in two South African tabloids : a compartive study of the Sowetan and Daily Sun Newspapers - Mabokela, Khutso Eunice (My University, 2018)
This is a comparative study on the coverage of the consumption of nyaope in two South African tabloid newspapers, namely the Sowetan and the Daily Sun. The study examines how the tabloids understudy reported on the consumption of the street drug; nyaope, by determining the frequency and nature of news reports, assessing the quality of the news reports and comparing the news reporting styles adopted by both newspapers. The research report draws from media effects theoretical propositions, namely the agenda setting and framing theories. Detailed literature review on tabloids and coverage of illicit drugs particularly nyaope is discussed in this study. The study adopted quantitative-qualitative as the research approach through the use of descriptive design. In addition, data were collected through quantitative-qualitative content analysis. The study used the check list as a method of collecting data. Subsequently, Interpretative Phenomenological Analysis (IPA) was adopted for the data analysis process. The study noted that the quality of any tabloid newspaper is centred on the manner in which it reports on societal issues like drug use and abuse, crime, health issues, politics, et cetera. The study results revealed that both tabloids’ frequency on the coverage of the consumption of nyaope was minimal as part of the requisite contribution towards combating drug use among young people. Furthermore, the study noted that the quality of news reports in both newspapers was truthful, accurate, fair, and balanced. The styles of news reporting indicated that the two newspapers made conscious efforts to avoid deliberate derogatory or discriminating references discriminatory towards nyaope users. In conclusion, the study examined the employment of mechanisms by the South African print media (tabloids) to ensure frequent, non-sensational, informed and detailed reporting, regarding issues on the consumption of illicit drugs particularly nyaope.
Thesis ((M. A. (Media Studies)) --University of Limpopo, 2018
Keywords: Tabloid newspapers; Nyaope consumption; Media; Drugs; Tabloid newspapers -- South Africa; Drugs and mass media; Drug abuse -- South Africa